Improving Food Security through Climate-Smart Farming and Readiness for Disasters - Silaswara, Diana; Chandra, Yopie; Mardiana, Harisa; Gini, Puti Lenggo (CV. Ulil Albab Corp, 2024)
This research investigates how residents, government officials, and farmers in Tangerang City, Banten, Indonesia perceive temperature, precipitation, and food security. By combining quantitative survey data with qualitative insights through a mixed-methods approach, a holistic view of stakeholder perspectives is achieved. Findings reveal that farmers have higher mean perceptions across all variables, indicating their heightened awareness and proactive stance toward climate-related challenges. Government officials also demonstrate consistent awareness of temperature and precipitation issues, reflecting their professional engagement. Residents exhibit diverse experiences and awareness levels, suggesting varying community perceptions Major disparities in understanding underscore the necessity of varied perspectives in tackling climate problems. Recommendations consist of expanding participant numbers, examining various data sets, enhancing the blend of qualitative and quantitative methodologies, engaging stakeholders throughout the research process, and fostering partnerships across fields for well-informed decision-making